Non-invasive, opsin-free mid-infrared modulation activates cortical neurons and accelerates associative learning - Zhang, Jianxiong; He, Yong; Liang, Shanshan; Liao, Xiang; Li, Tong; Qiao, Zhi; Chang, Chao; Jia, Hongbo; Chen, Xiaowei (Nature communications, 2021)
Neurostimulant drugs or magnetic/electrical stimulation techniques can overcome attention deficits, but these drugs or techniques are weakly beneficial in boosting the learning capabilities of healthy subjects. Here, we report a stimulation technique, mid-infrared modulation (MIM), that delivers mid-infrared light energy through the opened skull or even non-invasively through a thinned intact skull and can activate brain neurons in vivo without introducing any exogeneous gene. Using c-Fos immunohistochemistry, in vivo single-cell electrophysiology and two-photon Ca 2+ imaging in mice, we demonstrate that MIM significantly induces firing activities of neurons in the targeted cortical area. Moreover, mice that receive MIM targeting to the auditory cortex during an auditory associative learning task exhibit a faster learning speed (~50% faster) than control mice. Together, this non-invasive, opsin-free MIM technique is demonstrated with potential for modulating neuronal activity. Neurostimulant drugs or magnetic/electrical stimulation techniques have shown limited effects on learning capabilities of healthy subjects. The authors show that, without introducing an exogeneous gene, mid-infrared light can modulate firing activity of neurons in vivo and accelerate learning in mice.